2014
DOI: 10.1155/2014/925705
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Alanine/Arginine Mixture by Using TLC/FTIR Technique

Abstract: We applied TLC/FTIR coupled with mapping technique to analyze an alanine/arginine mixture. Narrow band TLC plates prepared by using AgI as a stationary phase were used to separate alanine and arginine. The distribution of alanine and arginine spots was manifested by a 3D chromatogram. Alanine and arginine can be successfully separated by the narrow band TLC plate. In addition, the FTIR spectra of the separated alanine and arginine spots on the narrow band TLC plate are roughly the same as the corresponding ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In these studies, by using reflection techniques, although it has been highlighted the diffuse reflectance (DRIFT), it was mentioned that there were difficulties related to time of analysis and interference of absorptions of materials used in DRIFT-TLC analysis, such as silica present on the TLC plate, with those relating to additives to be identified. Recently, FT-IR microscopy technique [11] , have been focused as more promising, but we think that other reflection techniques, less complex and quicker can be used, such as universal attenuated total reflection (UATR), which has been used successfully to polymer analysis at IAE laboratories [6] . Therefore, in this paper, it was evaluated the applicability of the coupling/association TLC /IR techniques for the analysis of two EPDM rubber compositions, aiming to contribute to increase for increasing the knowledge for characterization of additives in rubber by potential reflection techniques, such as UATR.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, by using reflection techniques, although it has been highlighted the diffuse reflectance (DRIFT), it was mentioned that there were difficulties related to time of analysis and interference of absorptions of materials used in DRIFT-TLC analysis, such as silica present on the TLC plate, with those relating to additives to be identified. Recently, FT-IR microscopy technique [11] , have been focused as more promising, but we think that other reflection techniques, less complex and quicker can be used, such as universal attenuated total reflection (UATR), which has been used successfully to polymer analysis at IAE laboratories [6] . Therefore, in this paper, it was evaluated the applicability of the coupling/association TLC /IR techniques for the analysis of two EPDM rubber compositions, aiming to contribute to increase for increasing the knowledge for characterization of additives in rubber by potential reflection techniques, such as UATR.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory results have been obtained. 29,30 All these work have demonstrated that TLC/FTIR by using AgI as stationary phase is applicable to real chemical systems.…”
Section: Introductionmentioning
confidence: 99%